Shaking table test and numerical analyses of a full scale three-leaf masonry wall - Francesco Di Michele; Enrico Spacone; Guido Camata; Giuseppe Brando; Anastasios Sextos; Adam Crewe; George Mylonakis; Matt Diez; Luiza Dihoru; Humberto Varum (Bulletin of Earthquake Engineering, 2023)
This paper discusses the main results of a full-scale shaking table test campaign carried out under the auspices of the EU funded research project SERA, whose objective is to investigate the seismic performance of three-leaf masonry walls with weak lime-mortar joints. These masonry walls are widely found in seismic prone regions in the Mediterranean area, thus assessing their behaviour under dynamic actions is an important pre-requisite for the seismic vulnerability evaluation of a plethora of historical centres. The first part of the paper presents a preliminary study on the mechanical properties of the wall component materials that was carried out through an ad-hoc experimental campaign. The outcomes are of particular interest for the characterization of the mortar and of the infill materials, that were designed to reproduce the low strength that is typically found in old masonry buildings. The design of the masonry wall that was tested and the test set-up are presented next. The applied loading protocol consisted of the horizontal component of a ground motion record that is repeatedly applied to the shaking table with increasing intensity. Finally, the main results of the experimental test are discussed. The damage patterns, drift ratios and base shear are presented for the ground motion sequence. The results are also discussed through a dynamic capacity curve that shows the attainment of different limit states with increasing ground motion intensity. A set of nonlinear numerical simulations, both static and dynamic, using a 3D FE model of the wall verify the experimental study as they report good agreement with the experimental tests and exhibit stable numerical behaviour.